Development of BIPA Teaching Materials Daily Communication Goals - Sutikno, Nonny Rulisty Putri; Suyitno, Imam; Roekhan, Roekhan (Graduate School of Universitas Negeri Malang, 2023)
Teaching materials for daily communication purposes are needed by BIPA students at the beginner level so they can establish social contact and communicate with native speakers. The development model in this study is the 4D development model. Daily communication material focuses on the use of formal and informal language as a tool for verbal communication. Based on the validation test that has been carried out for the total results of BIPA material expert validation of 67.5%. Practitioners 67.1%, and 79.1% graphic experts. Therefore, this teaching material is quite feasible to use.